Visitor spending in the Caribbean in 1986 - Arley, H. (CTRC Christ ChurchBB, 1987)
Provides estimates of expenditure by tourists and excursionists in the Caribbean on a country and regional basis for 1986. Contains comparable figures for the period 1980-1985. Discusses the economic importance of visitor expenditure to balance of payments, GDP, Government revenues and employment of Caribbean countries.